Analysis of Liquidity Ratio, Profitability Ratio and Solvency Ratio as a Tool in Measuring Financial Performance in PT Bank Mandiri (Persero) Tbk - Putri, Vanessa; Sari, Maya Macia (Journal of Community Research and Service, 2024)
This study aims to analyze the liquidity ratio, profitability ratio and solvency ratio as a tool in measuring financial performance at Bank Mandiri (Persero) Tbk for the period 2018-2022. The research method used is financial ratio analysis with a focus on Current Ratio, Loan to Deposit Ratio (LDR), return on asset (ROA) ratio, operating expenses to operating income (BOPO), CAR (Capital Adequacy Ratio) and DER Ratio (Debt to Equity Ratio). Overall the results showed that the financial performance of PT Bank Mandiri (Persero) Tbk was classified as healthy in terms of liquidity and solvency. However, the profitability of PT Bank Mandiri (Persero) Tbk still needs improvement.